2011
DOI: 10.1007/s11270-011-0850-5
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Seawater, Sediment, and Rock Oyster Saccostrea cucullata from the Northern Part of the Persian Gulf (Bushehr Province)

Abstract: The concentration of polycyclic aromatic hydrocarbons (PAHs) was determined in seawater, sediment, and Rock oyster Saccostrea cucullata collected from four sampling sites in the inter-tidal areas of Bushehr province. The total concentrations of 14 PAHs varied from 1.5 to 3.6 ng/L in seawater, 41.7 to 227.5 ng/g dry weight in surface sediment, and 126 to 226.1 ng/g dry weight in oyster tissue. In comparing PAH concentrations among the three matrices in Bushehr province, data showed that the pattern of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 37 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Due to both domestic and industrial human practices, organic micropollutants like polycyclic aromatic hydrocarbons (PAH) are detected at various concentrations in many environments like soils [ 1 , 2 ], sediments [ 3 5 ], waters [ 6 ] and biota [ 7 ]. They are produced by partial combustion of organic matter during fossil fuel or wood combustion, waste incineration, use of coal and petroleum refining and found in coal tar, crude oil, creosote, and roofing tar, or produced by dyes, plastics, and pesticides manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to both domestic and industrial human practices, organic micropollutants like polycyclic aromatic hydrocarbons (PAH) are detected at various concentrations in many environments like soils [ 1 , 2 ], sediments [ 3 5 ], waters [ 6 ] and biota [ 7 ]. They are produced by partial combustion of organic matter during fossil fuel or wood combustion, waste incineration, use of coal and petroleum refining and found in coal tar, crude oil, creosote, and roofing tar, or produced by dyes, plastics, and pesticides manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The loads of high molecular weight PAHs in sediment samples is more likely to be transported to the environment due to their increased absorption and degradation resistance properties (Mirza et al 2012). It has been well established that PAHs have carcinogenic, mutagenic and teratogenic effects on experimental animals (Hoffman and Wynder 1971, Grimmer 1983, Baek et al 1991, Perera 1997.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Many studies are regularly done on the shelf and in deep waters of the Gulf of Mexico (Gay et al, 2011;Aeppli et al, 2014), the Persian Gulf (Mirza et al, 2012;Monazami Tehrani et al, 2013), on the continental shelf and in the deep waters of Thailand (Boonyatumanond et al, 2006), along the western edge of the Bay of Bengal (Fernandes et al, 2014), the Bering Sea (Oguri et al, 2012;Moore et al, 2014) and in bottom sediments of the Chesapeake Bay in Virginia, USA (Kan et al, 2005). Other researchers have studied carbon-containing compounds in bottom sediments of the Ross Sea near the Antarc-tic coast (Villinski et al, 2000), in the Weddell Sea (Antarctica) (Rau et al, 1991), in the water mass and bottom sediments in the Atlantic and Pacific oceans (Kaiser and Benner, 2009) and in the Sargasso Sea (Sowell et al, 2009).…”
Section: Study Areamentioning
confidence: 99%
“…Near-surface exploration methods have been used with mixed success in petroleum exploration, which has led to discussions about the complex nature of hydrocarbon leakage in marine conditions. Numerous thematic studies have demonstrated the effectiveness of near-surface geochemical exploration methods (Villinski et al, 2000;Khoroshko et al, 2004;Gay et al, 2011;Kallmeyer et al, 2012;Mirza et al, 2012;Aeppli et al, 2014). However, additional studies are required to specify conditions of applicability of geochemical methods and to understand when these methods work, what effect the choice of equipment and analytical procedures has, what best suits a specific parameter of the marine system, and, most importantly, how to interpret the results properly.…”
mentioning
confidence: 99%